Value creation and stability in financial services: How should we regulate banks? - Krahnen, Jan Pieter; Lindblom, Ted; Lucas, Deborah; Olsson, Magnus; Fulghieri, Paolo; Thakor, Anjan (Journal of Financial Intermediation, 2025)
This paper is based on a panel discussion at the international bank conference on Frontier Risks, Financial Innovation and Prudential Regulation of Banks in Gothenburg, Sweden, June 2–4, 2024. The panelists were Deborah Lucas, Jan Pieter Krahnen, and Magnus Olsson, with Ted Lindblom moderating. This paper contains the panel presentations, along with a unifying discussion by Paolo Fulghieri and Anjan Thakor. The main themes in the paper focus on how society should balance costs and benefits in designing the prudential regulation of banks. Optimal regulation should take into account how banks and markets interact, the dangers of both under-regulation that spawns excessive risk-taking and over-regulation that depresses value-enhancing innovation in financial services, the somewhat fragmented nature of national-sovereignty-constrained European banking and financial markets regulation relative to bank regulation in the US, and how prudential regulation can be improved by more explicitly dealing with interest rate risk.